Analisis Evaluasi Keberlanjutan E-Filling di Kota Palembang - Dewi Sartika; Imelda Saluza (Jurnal Informatika Global)
AbstractDJP continues to optimize the collection of tax returns by facilitating a technology-based tax service system, one of which is e-filing that has been running since 2016. However, e-filing turned out to have less influence on the delivery of Tax Returns (SPT) as reflected in the electronic SPT monitoring data that only met 78% of the 2017 target. This is caused by various problems that arise during the use of e-filing such as individual technology capabilities, loss of efin, forgetting DJP Online account passwords to lack of awareness about the importance of submitting SPT. Problems encounter during the use of e-filing are the basis for evaluating the continued use of e-filling in Palembang. The development of a conceptual model was conducted to evaluate the sustainability of the use of e-filing. The development of a conceptual model basically has a scarcity of supporting theories used and has a complex model. To overcome this problem, Partial Least Squares (PLS) Structural Equation Model (SEM) could be applied to. The results of data analysis found that information quality and service quality did not have a positive influence on the sustainability of the use of e-filing and the level of correlation between information quality, system quality, service quality, and individual ability was still small towards the sustainability of the use of e-filing. The findings of this research are very important for the KPP Pratama in Palembang to analyze the sustainability of the use of e-filing that has been proven empirically, multidimensional and in a specific context. This knowledge could be used as a reference to improve overall quality of taxation for the sake of sustainable use of e-filing.Keywords : SPT, e-filing, PLS SEMAbstrakDJP terus berupaya mengoptimalkan pengumpulan Surat Pemberitahuan Tahunan (SPT) pajak dengan memfasilitasi sistem pelayanan perpajakan berbasis teknologi, salah satunya adalah e-filing yang telah berjalan sejak tahun 2016. Namun, e-filing ternyata kurang berpengaruh terhadap penyampaian SPT yang tergambar pada data hasil monitoring SPT elektronik yang hanya memenuhi 78% dari target sasaran tahun 2017. Hal ini disebabkan oleh berbagai masalah yang muncul selama pemanfaatan e-filing seperti kemampuan teknologi individu, kehilangan efin, lupa password akun DJP Online hingga kurangnya kesadaran tentang pentingnya penyampaian SPT. Permasalahan selama penggunaan e-filing menjadi dasar untuk melakukan evaluasi terhadap keberlangsungan penggunaan e-filling di Palembang. Pengembangan model konseptual dilakukan untuk mengevaluasi keberlanjutan penggunaan e-filing. Pengembangan model konseptual pada dasarnya memiliki kelangkaan teori-teori pendukung yang digunakan dan memiliki model yang kompleks. Untuk mengatasi masalah ini dapat menggunakan Partial Least Squares (PLS) Structural Equation Model (SEM). Hasil analisis data mendapatkan temuan bahwa kualitas informasi dan kualitas layanan tidak memiliki pengaruh positif terhadap keberlanjutan penggunaan e-filing dan tingkat korelasi antara kualitas informasi, kualitas system, kualitas layanan, dan kemampuan individual masih kecil terhadap keberlanjutan penggunaan e-filing. Temuan peneliti ini sangat penting bagi pihak KPP Pratama kota Palembang untuk menganalisa keberlanjutan penggunaan e-filing yang telah dibuktikan secara empiris, multidimensional dan konteks yang spesifik. Pengetahuan ini dapat dapat menjadi acuan untuk meningkatkan kualitas secara keseluruhan demi keberlanjutan penggunaan e-filing.Kata kunci : SPT, e-filing, PLS SEM,